Developing New Foodstuffs Using Microwave-cooked Cod Liver and Its Oil - Kovaleva, Olga; Dvoryankina, Christina; Volchenko, Vasily (KnE Life Sciences, 2020)
The non-sterilized cooked cod liver has been used as a novelty in the technology of culinary and making of sausage products. This cod liver has been cooked using microwave processing. The semi-finished cod liver oil separated during such microwave treatment has been also used for preparing such production. As for cooked boiled sausages, pork heart and venison have also been used in the composition with a view to enrich the nutritional value.